PEMODELAN INDEKS RISIKO KONFLIK PEMANFAATAN SUMBER DAYA LAUT DI ZONA EKONOMI EKSKLUSIF ASIA TENGGARA BERBASIS DATA PENGINDERAAN JAUH - Salsabilah, Fitda
Conflicts over the use of marine resources have an enormous impact on the maritime sector, politics, and economies of countries in the region. Losses due to the use of marine resources in the fisheries sector alone cause a loss of $5.8 billion per year. Spatial modelling is needed to estimated which areas have potential conflict risks. The strategic steps are developed by integrating remote sensing data. This study aims to develop a priority index to delineate the areas that have a potential conflict risk. The study utilizes three spatial modeling criteria: the outer exclusive economic zone boundary index, the fishing potential zone index, and the vessel activity index. The integration of the third value index is carried out using the Multi Criteria Decision Making (MCDM) method so as to produce 5 conflict risk index from very low until very high. The modeling results show that Indonesia's exclusive economic zone is the most conflict-prone marine area. The modeling of the conflict risk index in the South East Asian Exclusive Economic Zone results in very high class in the exclusive economic zones of Malaysia, Thailand, Indonesia, and Vietnam. This research is expected to support Sustainable Development Goals (SDGs), namely harmony among the marine constituents, justice for those that have been disadvantaged, and the establishment strong institutions going forward.